The Urgency Of Legal Protection Of Personal Data - Samin, Herol Hansen; Ismail, Dian Ekawaty; Rahim, Erman I (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
In a highly dynamic digital era, legal protection of personal data has become very important to ensure individual privacy and avoid security risks associated with the use of technology. In this context, legal protection of personal data on digital platforms becomes very urgent because personal data collected and processed by these digital platforms can be very sensitive and has the potential to invade individual privacy. In relation to telematics law, the legal protection of personal data on digital platforms must be reviewed from the perspective of telematics law which regulates the use of information and communication technology. Telematics laws place clear limits on the use of personal data and require digital platforms to adhere to high security and privacy standards. However, in practice, there are still many digital platforms that do not comply with telematics legal regulations related to personal data protection. They often collect and process personal data without explicit permission and do not provide users with clear information about how the data is used and stored. In this research, we will review the urgency of legal protection of personal data in digital platforms from the perspective of telematics law to analyze how telematics law regulates personal data protection and digital platforms must comply with these rules to ensure individual privacy. As well as the government's role in supervising and supervising digital platforms that do not comply with these regulations. Thus, this research is expected to contribute to a better understanding of the urgency of legal protection of personal data on digital platforms and how telematics law can be used to protect individual privacy in a very dynamic digital era